Filogenetik Kutu Penghisap Darah (Haematopinus sp.) pada Beberapa Jenis Sapi berdasarkan Gen 18S rRNA - Aan Awaludin; Yudhi Ratna Nugraheni; Mira Andriani; Niswatin Hasanah; Agus Hadi Prayitno (Jurnal Ilmu Peternakan Terapan, 2020)
The purpose of this study was to determine the phylogenetic relationship of Haematopinus sp. which became parasites in several types of cattle, namely Simmental, Limousin, PO (Peranakan Ongole), and FH (Friesian Holstein) from Jember Regency and Simmental and PO cattle from Karanganyar Regency. The method used was to isolate DNA from 6 samples of Haematopinus sp. and amplified using 18S rRNA universal primers with 18S (5'-TCATTACGAGCTCTGCAAT-3) reverse primers and 18S (5'-TTCAAAGTAAACGTGTCGGC-3) sequential PCR sequencing. Sequencing results were analyzed using MEGA 6 software for phylogenetic tree construction using the Neighbor-Joining and Maximum Parsimony Methods. The results showed that the sample Haematopinus sp. originating from Simmental, Limousin, and PO cattle from Jember, and Simmental and PO from Karanganyar were included in one cluster by Haematopinus quadripertusus. Haematopinus sp. sample from Jember FH cattle had a considerable genetic distance from Haematopinus quadripertusus which was possible because the sequence that could be analyzed was only 236 nt.